Rapid Prototyping of Three-dimensional (3-D) Daubechies with Transpose-based Method for Medical Image Compression - Ja'afar, Noor Huda; Ahmad, Afandi; Amira, Abbes (International Journal of Integrated Engineering, 2022)
This paper presents an efficient architecture for three-dimensional (3-D) Daubechies with transpose-based method for medical image compression. Daubechies 4-tap (Daub4) and Daubechies 6-tap (Daub6) are selected with pipelined direct mapping design technique. Due to the separability property of the multi-dimensional Daubechies, the proposed architectures have been implemented using a cascade of three N-point one-dimensional (1-D) Daub4/Daub6 and two transpose memories for a 3-D volume of N*N*N suitable for real-time 3-D medical imaging applications. The architectures were synthesised using VHDL and implemented on Altera®Cyclone II (EP2C35F672C6) field programmable gate array (FPGA). An in depth evaluation in terms of area, power consumption, maximum frequency and latency are discussed in this paper.